Symptomatic Urinary Tract Infections in Renal Transplant Recipients after Cystoscopy for Ureteral Stent Removal. Issue 5 (September 2017) - Gregg, Justin R.; Kang, Caroline L.; Talbot, Thomas R.; Moore, Derek; Herrell, Duke S.; Dmochowski, Roger; Barocas, Daniel A.
Abstract : Introduction: : Symptomatic urinary tract infection is a known complication of cystoscopy with ureteral stent removal. However, little is known about the incidence and risk factors for urinary tract infection after cystoscopy in renal transplant recipients, who likely represent a high risk cohort. In this study we determined the infection rate after cystoscopy with stent removal in this population and identified opportunities for care improvement. Methods: : We performed a retrospective cohort study of office cystoscopies with stent removal in renal transplant recipients performed at a single institution from April 2012 through May 2014. Strict criteria were used to determine the presence of symptomatic urinary tract infection within 1 month of the procedure. Fisher's exact tests were completed to examine associations between patient characteristics and post‐transplant outcomes with urinary tract infection. Results: : A total of 324 patients were included in the study. Mean age was 50.0 years (SD 13.1) and 187 patients (57.7%) were male. In this group 165 patients (52.5%) received an oral fluoroquinolone antibiotic before the procedure. Nine patients had symptomatic urinary tract infections (2.8%), of which 3 infections (33.3%) were due to quinolone‐resistant organisms. Female sex but no other patient or postoperative characteristic was associated with symptomatic urinary tract infection (p=0.04), including the use of peri‐procedural antibiotics. Conclusions: : The incidence of symptomatic urinary tract infection after cystoscopy with ureteral stent removal in renal transplant recipients is less than 3%, comparable to the risk of urinary tract infection after cystoscopy in the general population. Female sex is associated with symptomatic urinary tract infection. Further investigation is needed to identify the groups at greatest risk for urinary tract infection and other complications.